2017
DOI: 10.1002/jcop.21886
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of youth mentoring on student mentors' civic engagement attitudes and behavior

Abstract: The current study was designed to explore the delayed effect of participating in youth mentoring programs, training in civic engagement, and activism on a sample of 337 Israelis 5 to 10 years after serving as student mentors. Qualitative and quantitative findings showed that these former mentors' perception of the contribution of mentoring was correlated with their current civic engagement attitudes and activism. Further, the perceived quality of training during mentoring was correlated with the overall percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Virtual mentors described a number of positive outcomes resulting from their virtual mentoring experiences, including the reduction of biases and development of cultural humility, interpersonal growth, and a sense of civic responsibility. These domains of influence are consistent with findings from similar research studies examining the benefits mentors derive from their face‐to‐face relationships with youth (Anderson & Dubois, 2022; e.g., Duron et al, 2020; Goldner & Golan, 2017; Haddock et al, 2017; Hughes et al, 2009; Lee et al, 2017; Trepanier‐Street, 2007; Weiler et al, 2013; Weiler et al, 2014). Indeed, a recently published scoping review showed that qualitative explorations of how adults may be influenced by their experience mentoring youth have almost universally described positive growth or other desirable change (Anderson & Dubois, 2022).…”
Section: Discussionsupporting
confidence: 81%
“…Virtual mentors described a number of positive outcomes resulting from their virtual mentoring experiences, including the reduction of biases and development of cultural humility, interpersonal growth, and a sense of civic responsibility. These domains of influence are consistent with findings from similar research studies examining the benefits mentors derive from their face‐to‐face relationships with youth (Anderson & Dubois, 2022; e.g., Duron et al, 2020; Goldner & Golan, 2017; Haddock et al, 2017; Hughes et al, 2009; Lee et al, 2017; Trepanier‐Street, 2007; Weiler et al, 2013; Weiler et al, 2014). Indeed, a recently published scoping review showed that qualitative explorations of how adults may be influenced by their experience mentoring youth have almost universally described positive growth or other desirable change (Anderson & Dubois, 2022).…”
Section: Discussionsupporting
confidence: 81%
“…In particular, volunteering can meet volunteers' needs, such as career enhancement, learning new skills, building social relationship, escaping from negative feelings, and improving self-esteem (Clary et al, 1998;Smith et al, 2010). Moreover, in the field of education, volunteering plays a vital role in cultivating students' civic spirit and sense of social responsibility (Goldner & Golan, 2017;Lin, 2015;Rockenbach et al, 2014). Therefore, volunteering participation has gradually become a basic requirement for college students.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the reciprocal relationship of mentoring, mentors with ASD may also glean unique benefits. For instance, neurotypical mentors realize benefits in areas such as civic engagement, interpersonal skills, and self-esteem (Goldner & Golan, 2017; Weiler etal., 2013). Serving as a mentor could provide opportunity for social participation, an important avenue by which adults with ASD experience greater quality of life (Tobin etal., 2014).…”
mentioning
confidence: 99%